Cryptosphaeria Canker of Populus nigra Caused by Cryptosphaeria pullmanensis, a New Threat to Poplar Industry in Iran. Issue 6 (June 2017) - Rashid Aghdam, Abdulrahman; Babai‐Ahari, Asadollah; Karimi, Kaivan; Arzanlou, Mahdi
Abstract: Trunk diseases are potential threats to the poplar industry worldwide, including Iran. A survey on trunk diseases of Populus nigra in north‐western Iran revealed a new canker disease associated with dieback and decline of this host in West Azarbaijan Province of Iran. Wood samples were collected from poplar trees showing canker, dieback and decline symptoms and taken to the laboratory. A total of 173 fungal isolates were recovered from symptomatic tissues, of those 147 isolates had similar cultural and morphological features on potato dextrose agar. Based on a combination of morphological characteristics and phylogenetic inferences including DNA sequence data from the internal transcribed spacer regions (ITS1, 5.8S rDNA, and ITS2), all 147 isolates were identified as Cryptosphaeria pullmanensis . The remaining 26 isolates were identified as Cytospora chrysosperma . Pathogenicity of Cr. pullmanensis on two‐year‐old P .  nigra and Populus alba saplings under glasshouse conditions confirmed that Cr. pullmanensis is pathogenic on P. nigra and P. alba . Cryptosphaeria pullmanensis is here reported from Iran causing Cryptosphaeria canker on poplar trees for the first time. However, its host range, the extent of geographical distribution and management strategies remain to be examined.